OBESITY, INFLAMMATION, AND T-CELL METABOLISM - K. Hristov (Trakia Journal of Sciences)
Aim: The overview of the interdependence of the immune system and the system metabolism. Regulation of metabolism is immunomodulatory, and targeting key cellular metabolic enzymes impacts T-cell development, altering the immune functions. Background: The diet, gastrointestinal microbiota and the balanced function of liver, adipose and muscle tissues underlie the immune ecology. Chronic inflammation (macrophage, TH1, and TH17 T-cell infiltration) associates with obesity, and the development of metabolic syndrome, cardiovascular diseases, type 2 diabetes, IBD and intestinal malignancies. While naive T-cells use beta-oxidation, TCA cycle, and mitochondrial respiration to produce ATP, activated T-cells, similarly to cancer cells, employ the Warburg’s effect to power their function. The development of T-cells depends on key metabolic regulators, like mTORC1 (TH1 and TH17 T-cells) and mTORC2 (TH2 T-cells). Inhibition of HIF1-alpha (critical for TH17 T-cells) results in the development of FOXP3+ Treg T-cells, improving autoimmune disorders. Metabolic flexibility of normal cells underlines the successful treatment of neoplastic, autoimmune and hyper-sensitivity disorders. Conclusions: The immune system influences the system metabolism, and depends on the function of adipose tissue, muscles, liver, pancreas, lungs and gastro-intestinal tract. Diet and pharmacological regulation of T-cell metabolic activity influence immune function during autoimmunity, infections, and vaccinations.